Building industrial digital twins : design, develop and deploy digital twin solutions for real-world industries using Azure Digital Twins - Nath, Shyam Varan; Van Schalkwyk, Pieter (Packt Publishing, 2022)
Build your first digital twin MVP and gain first-hand experience of using the technology, the challenges it presents, and its impact on your organization About This Audiobook Create a digital twin prototype using Microsoft Azure Digital Twin Explore the digital twin approach to the design, operations, and maintenance of industrial assets and products Understand key characteristics and components of a digital twin through practical use cases and business scenarios In Detail Digital twin technology enables organizations to create digital representations of physical entities such as assets, systems, and processes throughout their life cycle. It improves asset performance, utilization, and safe operations and reduces manufacturing, operational, and maintenance costs. The audiobook begins by introducing you to the concept of digital twins and sets you on a path to develop a digital twin strategy to positively influence business outcomes in your organization. You'll understand how digital twins relate to physical assets, processes, and technology and learn about the prerequisite conditions for the right platform, scale, and use case of your digital twins. You'll then get hands-on with Microsoft's Azure Digital Twins platform for your digital twin development and deployment. The audiobook equips you with the knowledge to evaluate enterprise and specialty platforms, including the cloud and industrial IoT required to set up your digital twin prototype. Once you've built your prototype, you'll be able to test and validate it relative to the intended purpose of the twin through pilot deployment, full deployment, and value tracking techniques. By the end of this audiobook, you'll have developed the skills to build and deploy your digital twin prototype, or minimum viable twin, to demonstrate, assess, and monitor your asset at specific stages in the asset life cycle. Audience The digital twin audiobook is for mid-career subject experts, including engineers and operations managers, building their first prototype (MVP) using digital twin technology. The audiobook will help professionals responsible for mechanical, process, and reliability engineering domains. You don't have to be a developer or programmer, but beginner-level programming skills will be helpful.